A review of the effects of artificial light at night in urban areas on the ecosystem level and the remedial measures - Katabaro, Justine Mushobozi; Yan, Yonghong; Hu, Tao; Yu, Quan; Cheng, Xiang (Frontiers in Public Health, 2022)
This paper attempts to realize the balance between humans and ecology in designing the nighttime light environment of urban parks by clarifying the influence of nighttime artificial light on the ecosystem of urban parks. Firstly, we reviewed the effects of nighttime artificial light on individual predation and reproduction of animals and personal growth and reproduction of plants. Secondly, we discuss the impact of individual changes caused by artificial lighting on ecosystem function at the ecosystem and analyze its advantages and disadvantages. The results showed that nighttime artificial light had a double-sided impact on the ecosystem, which would hurt the ecosystem function, but had a positive effect on the green space, which lacked natural light and had high plant density. This paper focuses on the areas with increased application of artificial lighting and rich species of animals and plants in night cities, such as urban forest parks and urban green spaces. It discusses how to reduce the intrusion of artificial lighting on ecosystems and how to make better use of the positive effect of artificial light.